2022
DOI: 10.1186/s12936-022-04146-1
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of the diagnostic performance of EasyScan GO: a digital malaria microscopy device based on machine-learning

Abstract: Background Microscopic examination of Giemsa-stained blood films remains the reference standard for malaria parasite detection and quantification, but is undermined by difficulties in ensuring high-quality manual reading and inter-reader reliability. Automated parasite detection and quantification may address this issue. Methods A multi-centre, observational study was conducted during 2018 and 2019 at 11 sites to assess the performance of the EasyS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Most studies were only focusing on object-level or image-level evaluations so far. Even outside the scope of smartphone-based systems, only one such patient-level study [ 6 ] was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were only focusing on object-level or image-level evaluations so far. Even outside the scope of smartphone-based systems, only one such patient-level study [ 6 ] was found.…”
Section: Discussionmentioning
confidence: 99%
“…It can diagnose Plasmodium falciparum malaria by analysing a Giemsa-stained thick smear. Later, this prototype system evolved to a more advanced version and was renamed EasyScan Go [ 6 , 7 ], adding functions to diagnose non- P. falciparum species and an algorithm for thin smear analysis. Several other groups [ 8 10 ] also proposed systems with similar hardware designs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational models that accurately predict response to antiretroviral therapy have been developed and tested on cases of the disease from India and Southern Africa [6] . Machine learning has also been applied to the automated digital detection and quantification of malarial parasites, which could have a significant impact on the ability of laboratories in resource poor settings to diagnose and treat malaria [7] .…”
Section: Ai and The Sustainable Development Goalsmentioning
confidence: 99%
“…Hence, most systems yet used thin films, significantly reducing the sensitivity of the method. Nevertheless, most published studies reached a close-to or similar sensitivity and specificity as expert microscopy (Das et al, 2022 ; Knapper et al, 2022 ).…”
mentioning
confidence: 96%